2020
DOI: 10.1149/1945-7111/ab75fc
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Fast Proton Conduction by Dilution of a Hydronium Solvate Ionic Liquid: Localization of Ligand Exchange

Abstract: A dilution effect on the proton conduction of a hydronium solvate ionic liquid [H 3 O + •18C6]Tf 2 N, which consists of hydronium ion (H 3 O +), 18-crown-6-ether ligand (18C6), and bis[(trifluoromethyl)sulfonyl]amide anion (Tf 2 N-; Tf = CF 3 SO 2), has been studied. When [H 3 O + •18C6]Tf 2 N was diluted using equimolar 18C6 solvent, the distinctive fast proton conduction in [H 3 O + •18C6]Tf 2 N was suppressed in stark contrast to the case of common protic ionic liquids. Nuclear magnetic resonance spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…They are described as [H 3 O + •oligoether][Tf 2 N -] (oligoether = 18-crown-6 (18C6), dicyclohexano-18-crown-6 (Dh18C6), benzo-18-crown-6 (B18C6), and pentaethyleneglycol dimethylether (G5); Tf 2 N = bis (trifluoromethylsulfonyl)amide (Tf = SO 2 CF 3 )). [30][31][32][33] Here, each H 3 O + ion (solute) is solvated by oligoether ligands (solvent) to form a [H 3 O + •oligoether] complex cation (solvate), and the counter anion is the Tf 2 Nanion. These hydronium solvate ILs show interesting proton conduction behaviors.…”
Section: Ammonium (Nhmentioning
confidence: 99%
See 2 more Smart Citations
“…They are described as [H 3 O + •oligoether][Tf 2 N -] (oligoether = 18-crown-6 (18C6), dicyclohexano-18-crown-6 (Dh18C6), benzo-18-crown-6 (B18C6), and pentaethyleneglycol dimethylether (G5); Tf 2 N = bis (trifluoromethylsulfonyl)amide (Tf = SO 2 CF 3 )). [30][31][32][33] Here, each H 3 O + ion (solute) is solvated by oligoether ligands (solvent) to form a [H 3 O + •oligoether] complex cation (solvate), and the counter anion is the Tf 2 Nanion. These hydronium solvate ILs show interesting proton conduction behaviors.…”
Section: Ammonium (Nhmentioning
confidence: 99%
“…31 Although the ligand exchange conduction may be related to the strong acidity of [H 3 O + •18C6] cations -as indicated for some superacid-weak base mixtures 51 it is still unclear if the vehicle conduction can be attributed to the weak acidity of the [NH 4 + •18C6] cations. This is because ligand exchange conduction is absent in another analogous compound 32 which is a little more acidic than + and 0.44 for the H 3 O + compound). 30 These results can be explained by focusing on the ionicity, the value of Λ imp /Λ NMR .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The linear relationship between ln η or ln σ c and T –1 is provided in Figure S2c,d, obeying the Arrhenius law. The Walden plots, i.e., the plots of molar conductivity ( Λ imp ) versus fluidity ( η –1 ), are frequently used to evaluate how electrolytes are relatively conductive compared to ideal KCl aqueous solution. Figure shows the Walden plots of the AlCl 3 –G2 electrolytes together with the ideal KCl aqueous solution. The ratio of Λ imp / Λ ideal can be obtained from the difference in the vertical axis, i.e., log­( Λ imp / Λ ideal ), giving Λ imp / Λ ideal = 0.40 at all temperatures for x = 0.4.…”
Section: Resultsmentioning
confidence: 99%
“…Further, unlike common solvate ILs and protic ILs, this cooperative proton relay is suppressed and H3O + come to move as slow as 18C6 ligands when diluted using equimolar 18C6 solvent. 26 The proton conduction of the hydronium-based electrolytes would be interesting from the viewpoint of recently-proposed hydronium ion batteries 27,28 as well as fuel cells. 6,[13][14][15] In these studies, however, a key factor of the fast proton conduction has not been revealed.…”
Section: Introductionmentioning
confidence: 99%